Stress and immune system in fish - Urbinati, Elisabeth Criscuolo [UNESP] (2019)
The chapter presents the current knowledge about the organization and mechanisms of stress response in fish, and explores the factors that modulate the immune system during this response. In addition, the chapter discusses some strategies to reduce stress and combat pathogens, mainly with emphasis on Neotropical fish, as well as advances and future perspectives. Lastly, it helps us to have a better understanding of the complex neuroimmunoendocrine system and applications for fish production.